-5x-6.5>12
Add 6.5 to both sides...
-5x>18.5
Divide both sides by -5 and flip the sign...
x<-3.7
Answer:
9(4x - 1)
Step-by-step explanation:
The given linear expression is:
36x - 9
Since, 36 can be written as 9 times 4, we can rewrite the above expression as:
9(4x) - 9
Taking 9 as common, the expression changes to:
9 (4x - 1)
This linear expression can no linger be factorized further.
So,
36x - 9 = 9(4x - 1)
Brainliest for my virtuoso answer
Answer:
![5(x-3)(x-4)](https://tex.z-dn.net/?f=5%28x-3%29%28x-4%29)
Step-by-step explanation:
![5x^2-35x+60](https://tex.z-dn.net/?f=5x%5E2-35x%2B60)
Start by factoring out a 5:
![5(x^2-7x+12)](https://tex.z-dn.net/?f=5%28x%5E2-7x%2B12%29)
We need to find two integers that have a product of 12, and a sum of -7:
(-3)(-4)=12
-3-4=-7
We can split -7x into -3x and -4x
![5(x^2-3x-4x+12)](https://tex.z-dn.net/?f=5%28x%5E2-3x-4x%2B12%29)
Factor each half separately:
![5[x(x-3)-4(x-3)]](https://tex.z-dn.net/?f=5%5Bx%28x-3%29-4%28x-3%29%5D)
Since x and -4 are both being multiplied by x-3, we can combine them:
![5(x-3)(x-4)](https://tex.z-dn.net/?f=5%28x-3%29%28x-4%29)
Set the number of chickens as x and number of cows as <span>y
</span>so the farmer has total 28 animals
so x+y=28
you know that since the animals are healthy
chickens will have 2 legs and
cows will have 4 legs
the total number of legs are 64
so 2x+4y=64
since you want to find the number of cows
so from the first equation <span>x+y=28
</span>we will get another equation <span>x=28-y
</span>then plug into <span>2x+4y=64
2(28-y)+4y=64
56-2y+4y=64
56+2y=64
-56 -56
2y=8
y=4
</span>